2003
DOI: 10.1007/s00125-003-1059-y
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of increased concentrations of circulating glycated insulin in human Type 2 diabetes using a novel and specific radioimmunoassay

Abstract: Aims/hypothesis. Glycation of insulin, resulting in impaired bioactivity, has been shown within pancreatic beta cells. We have used a novel and specific radioimmunoassay to detect glycated insulin in plasma of Type 2 diabetic subjects. Methods. Blood samples were collected from 102 Type 2 diabetic patients in three main categories: those with good glycaemic control with a HbA 1c less than 7%, moderate glycaemic control (HbA 1c 7-9%) and poor glycaemic control (HBA 1c greater than 9%). We used 75 age-and sex-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 10 publications
2
15
1
Order By: Relevance
“…Hyperglycaemia can unbalance the redox status later in the disease and contribute to a vicious cycle by providing additional neoepitopes to which the immune system is not tolerant. Indeed, insulin glycation has been detected both in the pancreas in vivo [29] and in the serum of individuals with diabetes [30]. Interestingly, we did not observe increased reactivity to glycated insulin in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…Hyperglycaemia can unbalance the redox status later in the disease and contribute to a vicious cycle by providing additional neoepitopes to which the immune system is not tolerant. Indeed, insulin glycation has been detected both in the pancreas in vivo [29] and in the serum of individuals with diabetes [30]. Interestingly, we did not observe increased reactivity to glycated insulin in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, glycation of insulin and proinsulin has been found to occur in pancreatic b-cells contributing to bcell dysfunction in diabetic animal models [127]. Increased levels of circulating glycated insulin have been found in diabetic animal models and in humans with Type 2 diabetes, and this modified insulin showed reduced biological activity [128][129][130][131]. This potential of AGEs to exacerbate insulin resistance and abnormalities in glucose metabolism, will perpetuate excesses of methylglyoxal production and AGE formation, and the subsequent downstream detrimental effects on protein function.…”
Section: Ages and Insulin Resistancementioning
confidence: 99%
“…Insulin itself has been shown to be glycated within beta cells, resulting in impaired biological activity [129]. In a recent report, by using a specific radioimmunoassay, it was shown that glycated insulin circulates at higher concentration in Type 2 diabetic patients [130].…”
Section: Glycated Proteins and Advanced Glycated End Productsmentioning
confidence: 99%